Analisis Pengaruh Earning Per Share (EPS), Price Earning Ratio (PER) dan Return on Asset (ROA) Terhadap Harga Saham PT Bumi Serpong Damai Tbk Tahun 2008-2024 - Sampurno, Mahendra Dita; Sibarani, Mentiana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the effect of Earnings Per Share (EPS), Price Earnings Ratio (PER), and Return On Assets (ROA) on the stock price of PT Bumi Serpong Damai Tbk from 2008 to 2024. The research approach used is associative. This study employs 4 (four) variables consisting of 1 (one) dependent variable, namely stock price (close price), and 3 (three) independent variables, namely Earnings Per Share (EPS), Price Earnings Ratio (PER), and Return on Assets (ROA). The data analysis technique uses multiple linear regression analysis. The analysis results show that the independent variables (ROA, EPS, and PER) significantly influence the stock price of BSDE simultaneously (p<0.05), indicating that the overall fundamental condition of the company affects stock price determination. However, the t-test (partial) reveals that only EPS has a significant effect on the stock price (p<0.05), while the ROA and PER variables are not significant. This underscores that investors place more emphasis on the company's ability to generate earnings per share (EPS) as the primary benchmark for assessment. Theoretically, EPS is an indicator of profitability per share that directly reflects the potential return for shareholders, thus an increase in EPS tends to trigger a rise in stock price.